The Input Matters: Assessing Cumulative Language Access in Deaf and Hard of Hearing Individuals and Populations - Hall, Matthew L. (Frontiers in Psychology, 2020)
Deaf and hard-of-hearing (DHH) children present several challenges to traditional methods of language assessment, and yet language assessment for this population is absolutely essential for optimizing their developmental potential. Whereas assessment often focuses on language outcomes, this Conceptual Analysis argues that assessing cumulative language input is critically important both in clinical work with DHH individuals and in research / public health contexts concerned with DHH populations. At the individual level, paying attention to the input (and the person’s access to it) is vital for discriminating disorder from delay, and for setting goals and strategies for reaching them. At the population level, understanding relationships between cumulative language input and resulting language outcomes is essential to the broader public health efforts aimed at identifying strategies to improve outcomes in DHH populations and to theoretical efforts to understand the role that language plays in child development. Unfortunately, several factors jointly result in DHH children’s input being under-described at both individual and population levels: for example, overly-simplistic ways of classifying input, and the lack of tools for assessing input more thoroughly. To address these limitations, this Conceptual Analysis proposes a new way of characterizing a DHH child’s cumulative experience with input, and outlines the features that a tool would need to have in order to measure this alternative construct.